Lip Repositioning with Internal Suturing and Crown Lengthening in a Single Visit: Case Report - Dik Mega Putri Handayani; Vidya Nursolihati; Osa Amila Hafiyyah (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: A gummy smile becomes one of the esthetic problems for patients, especially when smiling or laughing. Etiology-based treatment should be considered to fulfill the patient’s needs. In this case report, we performed treatment focused on both extraoral and intraoral etiology: lip repositioning with smile elevator muscle sutures and crown lengthening respectively. Case: A 27 year old female patient presented with the chief complaint of excessive appearance of gingiva when especially laughing. The patient has a gummy smile and a disharmonious gingival line on the anterior maxilla. The diagnosis in this case was excessive gingival display et causa hyperactive upper lip and altered passive eruption. Case treatment: To achieve the esthetic goal, crown lengthening was performed with ostectomy to correct the gingival line and zenith, followed by lip repositioning with partial thickness flap with smile elevator muscle suturing. Six months postoperative follow-up showed pink gingiva with harmonious gingival line contour. Discussion: Lip repositioning has a high risk of relapse in cases of hyperactive upper lip. Lip reposition surgery with sutures on the smile elevator muscle along with a crown lengthening procedure is a predictable alternative treatment in this case. Conclusion: The surgical procedure for handling gummy smile cases provides good treatment results, especially in cases of multiple etiologies of hyperactive upper lip and altered passive eruption.